Application of the COSO Framework in Internal Control of University Cooperatives: A Comparative Case Study in Indonesia - Ihrom Caesar Ananta Putra; Rr. Tiara Amelia; Ratih Rakhmawati (Innovation Business Management and Accounting Journal, 2026)
This study aims to explore the application of COSO framework-based internal control in university cooperatives in Indonesia. This study uses a qualitative approach with a comparative case study strategy in three university cooperatives. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using thematic analysis to identify patterns, compare practices between cooperatives, and interpret internal control dynamics. Validity was strengthened through triangulation of sources and methods, member checking, and audit trails. Findings indicate variations in the implementation of internal controls. The STIE Mandala Cooperative still faces fundamental weaknesses, particularly in risk assessment and control activities, which are more administrative than substantive in nature. In contrast, the Artha STIESIA Employee Cooperative demonstrates good practices with the involvement of professionally competent supervisors, resulting in more substantive risk assessment and monitoring. The Muhammadiyah University Jember Employee Cooperative exhibits more systematic governance through formal document validation, competency-based personnel placement, and performance-based monitoring. This study confirms that effective internal control in university cooperatives requires a combination of a healthy organizational culture, formal document-based governance, expert involvement, and an integrated information system. The practical implication is the need to strengthen cooperative governance through document validation, utilization of competent human resources, and implementation of performance-based monitoring mechanisms to improve transparency and accountability. This study makes an original contribution by examining the application of the COSO framework in the context of university cooperatives in Indonesia, which has been relatively rarely studied. The comparative qualitative approach allows for an in-depth exploration of social and institutional dynamics, thereby broadening theoretical understanding and offering practical recommendations for strengthening member-based cooperative governance.